Asclepius and Epidaurus: The Sapiential Medicine as Divinatory Art. Between Therapeutic Landscapes and Healing Dreams - Bragazzi, Nicola Luigi; Martini, Mariano; Zerbetto, Riccardo; Re, Tania (Cosmos and History: The Journal of Natural and Social Philosophy, 2019)
Epidaurus was in the antiquity a therapeutic complex which included several buildings to which people came from every part of Greece to be cured by the god Asclepius, a deity venerated from 500 before Christ to the fourth-fifth century anno Domini, when many other pagan cults had already ceased to exist. Epidaurus was a very complex structure, a sort of city-state or sovereign state, able to host thousands of adepts. Here, patients were subject to ablution, purification and sporadic fasting. Asclepius appeared in a dream, in a sort a practice of magic-ritual and sapiential medicine.